Теплоаккумулирующая панель для поддержания микроклимата в помещении с радиоэлектронным оборудованием - Трофимов, В.Е. (Технология и конструирование в электронной аппаратуре, 2017)
Для поддержания микроклимата в помещениях с радиоэлектронным оборудованием, расположенных в труднодоступных регионах, предлагается для минимизации энергозатрат использовать теплоаккумулирующую панель, в которой происходит фазовый переход твердого рабочего вещества в жидкое под воздействием солнечного излучения. Приведены результаты оценки работоспособности такого устройства, характеристики и рекомендации по применению. Для підтримки мікроклімату в приміщеннях з радіоелектронним обладнанням, розташованих у важкодоступних регіонах, пропонується для мінімізації енерговитрат використовувати теплоакумулюючу панель, в якій відбувається фазовий перехід твердої робочої речовини в рідку під впливом сонячного випромінювання. Наведено результати оцінки працездатності такого пристрою, характеристики і рекомендації щодо застосування. In a number of applications the functioning of radio electronic equipment (REO) occurs in rooms located in hard-to-reach regions with climatic conditions that are characterized by significant air temperature fluctuations reaching tens of Celsius degrees. To compensate these fluctuations various microclimate control devices are used. Their common property is necessity to consume electric energy, amount of which in the specified conditions is sufficiently limited. In this regard, the actual task is to minimize energy costs to provide the microclimate REO, for example, by using devices that do not require electrical energy for their operation. One of the opportunities for solving this problem is using of a thermal-accumulating panel (TAP). It is designed to compensate heat losses from the room with REO at night. The principle of the TAP is based on the absorption and conservation of thermal energy for a period of time during the phase transition of a solid working substance into liquid influenced, for example, by solar radiation. The construction of such TAP is considered here. Assessments of its operability, characteristics and recommendations for use are given. It is shown that at air temperature of 20 ... 25 С TAP can heat the room for at least 4.6 ... 6.2 hours at 2.5 ... 4.5 hours of sunny weather during daylight hours.